Проблемы методологии педагогики в условиях инновационного развития образовательных систем на уроках физики - Алдашева, Д.Т. (My University, 2016)
The articleis devoted to themethodological problems ofthe modern educational space. This article provides thedefinition of the term"methodology"from the different author’s pointof view. Problems andsome form forms of resolution. We analyze theform and content ofthe curriculum.
Keywords: Methodology; problem-based learning; scientific approach; problems; regulation forms.